Comparative study of the cephalic trichobothria in plant bugs (Hemiptera: Heteroptera: Miridae). (October 2020) - Taszakowski, Artur; Gorczyca, Jacek; Herczek, Aleksander
Highlights: Cephalic trichobothria in plant bugs were thoroughly examined for the first time. A pair of ventral cephalic trichobothria is a characteristic feature of Miridae. Dorsal cephalic trichobothria in plant bugs were found for the first time. Scanning electron microscopy is a tool that enables the discovery of many new and significant morphological features. Abstract: A pair of ventral cephalic trichobothria was observed for the first time and so far the only one in a representative of single species of Miridae ( Fulvius carayoni ) in 2013. The purpose of our research was to verify the hypothesis that this is not an exception, but a characteristic feature of all plant bugs. Twenty-three representatives of all seven subfamilies of Miridae were examined using a scanning electron microscope. The results presents detailed data on the distribution and ultramorphology of the cephalic trichobothria in plant bugs. A pair of ventral cephalic trichobothria was observed in all of the examined species. Each trichobothrium of this pair is located laterally to the first article of the rostrum, on the gula (between the buccula and the antennal tubercle). Moreover, a pair of dorsal cephalic trichobothria was observed for the first time. They were found in nine species, located above the antennal tubercle, towards the center of the frons.